FAKTOR – FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN KANTOR PUSAT PT. AGRO SINERGI NUSANTARA - Nurmala Dewi; Nabila Hilmy Zhafira (Fakultas Ekonomi Universitas Warmadewa, 2022)
This study was conducted determine the effect of transformational leadership style (X1) and employee engagement (X2) on employee performance (Y) at the head office PT Agro Sinergi Nusantara. The method used in this study is a quantitative method. Data collection was carried out by distributing questionnaires with 30 employees as respondents at the head office of PT Agro Sinergi Nusantara. While the data analysis in this study using multiple regression analysis test. The result of the study show : 1) There is a positive and significant influence between transformational leadership style and employee engagement on the performance of PT Agro Sinergi Nusantara head office employee engagement which is shown from the F test result of 21,340 and a significance value 0,000b. 2) There is negative and insignificant effect between leadership style on employee performance as seen from t-test result of – 0,318 and significance value of 0,753. 3) There is a positive and significant effect between employee engagement on employee performance as seen from the t-test of 4,969 and a significance value of 0,000. The result of study were obtained with the regression equation Y = 14,,641a – 0,050X1 + 0,844X2 + e, and the effect was 61,3% and The remaining 38,7%was influenced by variables outside the study.